From Mouth to Screen: A Theoretical Framework for Digital Folklore as Vernacular Ecology, Social Validation, and Platform Behavior - Mohd Bahaudin Ihsan; Sri Maryani (Journal of Literary and Linguistic Research, 2026)
This article develops a theoretical framework of digital folklore as vernacular ecology, social validation system, and platform-mediated behavioral structure within contemporary participatory media environments. The study employs a non-empirical qualitative design based on systematic literature synthesis from folklore studies, media communication theory, and digital culture scholarship. Findings indicate that digital folklore emerges through ecological configurations of vernacular practices shaped by distributed participation, algorithmic mediation, and infrastructural constraints that reorganize cultural expression beyond territorial boundaries. Social validation operates as a ritualized mechanism in which engagement metrics such as likes, shares, and comments function as contemporary forms of communal recognition, reinforcing repetitive cultural patterns and stabilizing meaning across networks. Platform behavior further structures folkloric production through algorithmic ranking, interface design, and recommendation systems that selectively amplify certain expressive forms while marginalizing others. The study concludes that digital folklore is not merely a transformation of traditional folklore into digital media, but an emergent cultural system generated through the interaction of users, platforms, and computational logics. The proposed framework integrates repetition, variation, and validation as core analytical principles for understanding vernacular culture in digital ecosystems and contributes to methodological refinement in digital humanities and folklore studies.